Da responsabilidade civil do empreiteiro pelos defeitos na construção de imóveis: - Neto, Sara (2023)
In accordance with Article 1207 of the Civil Code, “Works Contract is the agreement by which one party undertakes, in relation to the other, to carry out a certain work for a price.” This research focuses on the legal analysis of the works contract in Private Law, with a focus on the regime of defects in the work. Considering the breadth of this legal framework, the subject of this study is limited to new construction projects. The main purpose of this dissertation is to expose the main issues that are the subject of doctrinal and jurisprudential disagreements related to defects in the work, particularly in properties intended for long-term use. In addition, special focus is paid to on aspects that have been less developed in doctrine, specifically those concerning properties subject to horizontal property regimes. The existence of so many topics subject to doctrinal and jurisprudential disagreements is justified by the fact that both regimes are provided for in a single article. In this context, the dissertation culminates in a proposal for legislative amendments to the Civil Code regime, based on the deepening of topics related to this subject, leveraging the remedies suggested by Decree-Law No. 84/2021, of October 18, which deals with consumer works contracts, which will be developed throughout this dissertation. To that end, the first chapter highlights some key concepts through introductory notes that summarize the regime of long-term properties, covering the historical background of long-term properties and ending with the specificities of the special regime for properties subject to horizontal property regimes. The same chapter is dedicated to the investigation of common works contracts, delving into the regime established in Article 1225 of the Civil Code. The presentation of the explored topics closely follows the organization adopted in the article itself. Regarding consumer works contracts, which are addressed in the second chapter of this dissertation, a detailed exploration of Decree-Law No. 84/2021, the main legislation on this matter, was carried out. The analysis of the entire property regime provided for in the aforementioned legislative decree is crucial, as it recently came into force (on January 1, 2022) and introduces some novelties into the national legal system that require careful study. Finally, in the third chapter, consolidating all the knowledge acquired throughout the research, a legislative amendment is suggested with the intention of resolving the issues that are the subject of disagreements. Its aim being to establish a regime that is predominantly subject to the interpreter's adoption of the remedy that best suits the situation, disregarding the treatments given to similar cases.